2020
DOI: 10.3390/ijerph17207645
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support and Crisis-Focused Psychological Interventions Designed to Mitigate Post-Traumatic Stress Injuries among Public Safety and Frontline Healthcare Personnel: A Systematic Review

Abstract: Public safety personnel (PSP) and frontline healthcare professionals (FHP) are frequently exposed to potentially psychologically traumatic events (PPTEs), and report increased rates of post-traumatic stress injuries (PTSIs). Despite widespread implementation and repeated calls for research, effectiveness evidence for organizational post-exposure PTSI mitigation services remains lacking. The current systematic review synthesized and appraised recent (2008–December 2019) empirical research from 22 electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 42 publications
5
89
0
3
Order By: Relevance
“…The authors also determined that there are no validated mental health interventions being implemented in this population and workplaces typically do not evaluate their programing using accepted methods, therefore, evidence for effectiveness of individual and interpersonal mental health programming is lacking [ 13 ]. This finding is supported by a recent systematic review focused on peer support and crisis-focused interventions implemented among PSP and healthcare personnel [ 14 ]. The authors found that the majority of the studies included in their review did not conduct pre-post evaluations and used inconsistent outcome measures which resulted in poor quality of evidence of the effectiveness of such interventions [ 14 ].…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…The authors also determined that there are no validated mental health interventions being implemented in this population and workplaces typically do not evaluate their programing using accepted methods, therefore, evidence for effectiveness of individual and interpersonal mental health programming is lacking [ 13 ]. This finding is supported by a recent systematic review focused on peer support and crisis-focused interventions implemented among PSP and healthcare personnel [ 14 ]. The authors found that the majority of the studies included in their review did not conduct pre-post evaluations and used inconsistent outcome measures which resulted in poor quality of evidence of the effectiveness of such interventions [ 14 ].…”
Section: Introductionsupporting
confidence: 62%
“…This finding is supported by a recent systematic review focused on peer support and crisis-focused interventions implemented among PSP and healthcare personnel [ 14 ]. The authors found that the majority of the studies included in their review did not conduct pre-post evaluations and used inconsistent outcome measures which resulted in poor quality of evidence of the effectiveness of such interventions [ 14 ].…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations